Rancang Bangun Smartlock Detection Berbasis Mikrokotroller Dan ESP8266 Sebagai Bahan Media Pembelajaran Laboratorium Teknik Informatika Dan Komputer: Studi Kasus Akademi Teknologi Bogor - Nahampun, Rajin; Sewaka; Taswanda Taryo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Pamulang, 2025)
The development of science and technology, many microcontroller-based innovations and the Internet of Things (IoT) that can be used as knowledge and practicum materials or learning media in a laboratory, while the Bogor Academy of Technology has an Informatics and Computer Technology laboratory which is currently in need additional facilities and facilities as student learning media based on microcontrollers and Internet of Things (IoT)-based smart locks, therefore the authors developed a prototype smartlock detection or Internet of Things (IoT)-based intelligent key detection as a complement to microcontroller-based student learning media in the laboratory Technology and Information Technology Bogor Academy of Technology, with the aim that the results of this study can be used as additional learning media regarding microcontroller-based smart keys. As for the development of this research, the authors analyze and use various information through journals and previous literature studies based on microcontrollers and IoT-based smart keys as references in the development of this research. With a descriptive research methodology, the results of this study can be used as complementary facilities and tools in overcoming the shortage of microcontroller-based learning media in the microcontroller-based and Internet of Things (IoT) Information and Computer Technology laboratory at the Bogor Academy of Technology in particular, and for readers in general.